2020
DOI: 10.3389/fnut.2020.583608
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Features Associated With a High-Fat/Low-Fiber Diet in Healthy Adults

Abstract: A high intake of dietary saturated fatty acids (SFAs) is related to an increased risk of obesity, inflammation and cancer-related diseases, and this risk is attenuated only when SFAs are replaced by unsaturated fats and unrefined carbohydrates. The gut microbiota has recently emerged as a new environmental factor in the pathophysiology of these disorders, and is also one of the factors most influenced by diet. We sought to determine whether the gut microbiota of healthy individuals whose intake of SFAs exceeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 68 publications
6
55
0
Order By: Relevance
“…Another study found that dried plum feed supplement in birds can mitigate heat stress by changes in microbiota, increasing bacteria such as Anaerotruncus , among others [ 76 ]. On the other hand, a high saturated fat/low fiber diet was associated with a greater sequence abundance of the Anaerotruncus genus, a butyrate producer associated with obesity [ 77 ]. The possible association of Anaerotruncus and epilepsy remains to be explored.…”
Section: Resultsmentioning
confidence: 99%
“…Another study found that dried plum feed supplement in birds can mitigate heat stress by changes in microbiota, increasing bacteria such as Anaerotruncus , among others [ 76 ]. On the other hand, a high saturated fat/low fiber diet was associated with a greater sequence abundance of the Anaerotruncus genus, a butyrate producer associated with obesity [ 77 ]. The possible association of Anaerotruncus and epilepsy remains to be explored.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has found the Anaerotruncus and Alistipes genera enriched in genetically obese (ob/ob) mice exhibiting severe glycolipid metabolism disorders relative to wild type and ob/ob mice consuming inulin with improved metabolic parameters [76,77]. Abundance of these two genera was also linked with consumption of high-fat diets in humans [78][79][80]. Altogether, these studies suggest that Anaerotruncus and Alistipes may directly or indirectly contribute to the metabolism of dietary fats and fiber types and community context influence this dynamic.…”
Section: Gene Expression In Liver Is Associated With Abundance Of Gut Bacterial Taxamentioning
confidence: 99%
“…Various external environmental factors, especially diet containing high carbohydrates, high protein, and high fat affect the gut microbiota dysbiosis and metabolic dysregulation [ 69 , 70 ]. Disturbed metabolic dysregulation due to high consumption of carbohydrate and fat diet increases the chances of obesity and relative abundance of pathogenic microbiota [ 71 , 72 ]. Consumption of high carbohydrates, high-protein, high-fat, and/or high-vitamin diets influences maternal extra and intrauterine factors by their pathogenic microbiota and metabolites, thereby increasing the risk of PTB [ 23 , 73 ].…”
Section: Microbiota Metabolites Pathological Insight In Ptbmentioning
confidence: 99%